Finanse Rady Głównej Opiekuńczej i jej struktur terenowych w latach 1918–1921 - Przeniosło, Małgorzata (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
Central Welfare Council [CWC] was formed in December 1915 in Warsaw. Its activities covered part of the Kingdom of Poland, which, after the dislodged of Russian’s army from this area, was occupied by the Germans. In Polish lands, it was one of the largest social self-organization. It had mainly to provide support to people in difficult circumstances in life. Self-help organizations are characteristic of the years of World War I, but the CWC continues its mission even after Poland regained its independence. The „new” CWC quickly developed a network of local structures in the former Austrian occupation. After Poland regained its independence, the CWC’s founds the majority came from subsidies provided by the state. The most significant were the grants of the Ministry of Labour and Social Welfare, support also followed from other ministries, especially the Ministry of Public Health. Some of the regional structures received support from local governments, especially district councils. CWC some of its resources received also tkanks to the generosity of the public, although it was lower than during the war. The detection of financial shortcoming caused the unfriendly atmosphere around the CWC and resulted in the decision of dissolving, which was taken at the session of the Council of Ministers in 8.12.1920.